High proportion strontium-doped micro-arc oxidation coatings enhance early osseointegration of titanium in osteoporosis by anti-oxidative stress pathway - Xinkun Shen (KeAi Communications Co., Ltd., 2022)
The excessive accumulation of reactive oxygen species (ROS) under osteoporosis precipitates a microenvironment with high levels of oxidative stress (OS). This could significantly interfere with the bioactivity of conventional titanium implants, impeding their early osseointegration with bone. We have prepared a series of strontium (Sr)-doped titanium implants via micro-arc oxidation (MAO) to verify their efficacy and differences in osteoinduction capabilities under normal and osteoporotic (high OS levels) conditions. Apart from the chemical composition, all groups exhibited similar physicochemical properties (morphology, roughness, crystal structure, and wettability). Among the groups, the low Sr group (Sr25%) was more conducive to osteogenesis under normal conditions. In contrast, by increasing the catalase (CAT)/superoxide dismutase (SOD) activity and decreasing ROS levels, the high Sr-doped samples (Sr75% and Sr100%) were superior to Sr25% in inducing osteogenic differentiation of MC3T3-E1 cells and the M2 phenotype polarization of RAW264.7 cells, thus enhancing early osseointegration. Furthermore, the results of both in vitro cell co-culture and in vivo studies also showed that the high Sr-doped samples (especially Sr100%) had positive effects on osteoimmunomodulation under the OS microenvironment. Ultimately, the collated findings indicated that the high proportion Sr-doped MAO coatings were more favorable for osteoporosis patients in implant restorations.